Dynamically pre-trained deep recurrent neural networks using environmental monitoring data for predicting PM2.5. Issue 6 (August 2016) - Ong, Bun; Sugiura, Komei; Zettsu, Koji
Abstract Fine particulate matter ( PM_2.5 PM 2.5 ) has a considerable impact on human health, the environment and climate change. It is estimated that with better predictions, US9 billion can be saved over a 10-year period in the USA (State of the science fact sheet air quality.http://www.noaa.gov/factsheets/new, 2012). Therefore, it is crucial to keep developing models and systems that can accurately predict the concentration of major air pollutants. In this paper, our target is to predict PM_2.5 PM 2.5 concentration in Japan using environmental monitoring data obtained from physical sensors with improved accuracy over the currently employed prediction models. To do so, we propose a deep recurrent neural network (DRNN) that is enhanced with a novel pre-training method using auto-encoder especially designed for time series prediction. Additionally, sensors selection is performed within DRNN without harming the accuracy of the predictions by taking advantage of the sparsity found in the network. The numerical experiments show that DRNN with our proposed pre-training method is superior than when using a canonical and a state-of-the-art auto-encoder training method when applied to time series prediction. The experiments confirm that when compared against the PM_2.5 PM 2.5 prediction system VENUS (National Institute for Environmental Studies. Visual Atmospheric Environment Utility System.http://envgis5.nies.go.jp/osenyosoku/, 2014), our technique improves the accuracy of PM_2.5 PM 2.5 concentration level predictions that are being reported in Japan.